2014
DOI: 10.1002/jbt.21598
|View full text |Cite
|
Sign up to set email alerts
|

Lophirones B and C Extenuate AFB1‐Mediated Oxidative Onslaught on Cellular Proteins, Lipids, and DNA through Nrf‐2 Expression

Abstract: The capability of lophirones B and C to extenuate aflatoxin B1 (AFB1)-mediated onslaught on cellular proteins, lipids, and DNA was investigated for 6 weeks. Lophirones B and C significantly (P < 0.05) increase the expression and specific activity of cytoprotective enzymes (glutathione-S-trans-ferase, nioctinamide adenine dicludeotide:quinone oxidoreductase-1, epoxide hydrolase, and uridyl glucuronosyl transferase). There was significant (P < 0.05) reduction in the level of antioxidant system in AFB1-induced he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 51 publications
3
18
0
Order By: Relevance
“…The attenuation of acetaminophen-mediated FIGURE 3. Proposed mechanism of action of lophirones B and C. 1: Lophirones B and C inhibits the acetaminophen activation through CYP 2E1 inhibition; 2: Further metabolism of NAPQI generates superoxide anion radical and nitric oxide; 3: Lophirones B and C enhanced detoxification of superoxide anion radical to hydrogen peroxide through increased superoxide dismutase; 4: Hydrogen peroxide is detoxified to water through enhanced (a) catalase and (b) glutathione peroxidase activities; 5: GSH used up by glutathione peroxidase action is replenished through glutathione reductase; 6: The reducing equivalent that keeps the antioxidant system in a coordinated manner is supplied by NADPH by the action of glucose 6-phosphate dehydrogenase; 7: Lophirones B and C prevent the formation of hydroxyl radical; 8: protein oxidation, lipid peroxidation and DNA damage that could result from hydroxyl radical is inhibited by lophirones B and C; 9: Nitric oxide generated during metabolism of NAPQI enhances the release INF-α and INF-β; 10: This release leads to the activation of Kupfer cells and 11: subsequent increase in IL-6, IL-8 and TNF-α which is inhibited by lophirones B and C lipid peroxidation documented in this study is in line with previous study [13].…”
Section: Lipid Peroxidationsupporting
confidence: 94%
See 1 more Smart Citation
“…The attenuation of acetaminophen-mediated FIGURE 3. Proposed mechanism of action of lophirones B and C. 1: Lophirones B and C inhibits the acetaminophen activation through CYP 2E1 inhibition; 2: Further metabolism of NAPQI generates superoxide anion radical and nitric oxide; 3: Lophirones B and C enhanced detoxification of superoxide anion radical to hydrogen peroxide through increased superoxide dismutase; 4: Hydrogen peroxide is detoxified to water through enhanced (a) catalase and (b) glutathione peroxidase activities; 5: GSH used up by glutathione peroxidase action is replenished through glutathione reductase; 6: The reducing equivalent that keeps the antioxidant system in a coordinated manner is supplied by NADPH by the action of glucose 6-phosphate dehydrogenase; 7: Lophirones B and C prevent the formation of hydroxyl radical; 8: protein oxidation, lipid peroxidation and DNA damage that could result from hydroxyl radical is inhibited by lophirones B and C; 9: Nitric oxide generated during metabolism of NAPQI enhances the release INF-α and INF-β; 10: This release leads to the activation of Kupfer cells and 11: subsequent increase in IL-6, IL-8 and TNF-α which is inhibited by lophirones B and C lipid peroxidation documented in this study is in line with previous study [13].…”
Section: Lipid Peroxidationsupporting
confidence: 94%
“…In support of this finding, lophirones B and C have been reported to attenuate AFB 1 -mediated decrease in antioxidant enzymes by enhancing the expression of Nrf-2 and antioxidant enzymes [13]. Furthermore, acetaminophen-mediated reduction in GSH could be due to accumulated NAPQI, which depletes GSH level [4,25,27].…”
Section: Antioxidant Enzymesmentioning
confidence: 71%
“…The decreased antioxidant enzyme (SOD, CAT, GSH‐Px, GSH‐red and Glc 6‐PD) activities in the liver of rats fed high‐fructose diet could lead to tissue damage and cell death . The attenuation of the decrease may be due to the capability of H. sabdariffa extract to enhance ROS‐detoxifying enzymes, possibly through redox transcription factors . The GSH and GSSG levels are widely used indicators of cellular redox state.…”
Section: Discussionmentioning
confidence: 99%
“…The AFB 1 -mediated decrease in the activities of these enzymes in rat hepatocytes, attributed to overwhelmed antioxidant enzymes, indicates oxidative stress arising from ROS (superoxide anion and nitric oxide) generated. The attenuation of AFB 1 -mediated decrease in the activities of these enzymes (SOD, CAT, GSH-Px and GSH-red) in rat hepatocytes shows the capability of lophirones B and C to prevent oxidative stress possibly by enhancing Nrf-2 expression (Ajiboye et al 2014c). Meki et al (2004) reported similar reversal of AFB 1 -mediated decrease in antioxidant enzymes following treatment of rats with melatonin.…”
Section: Oxidative Stressmentioning
confidence: 97%
“…Also, lophirones B and C enhance the expressions and activities of ROS and electrophilic species through the nuclear erythroid-related factor-2 (Nrf-2) (Ajiboye et al 2014b). These enhanced expressions and activities prevent oxidative stress, lipid peroxidation and DNA fragmentation in AFB 1 -induced hepatocarcinogenesis (Ajiboye et al 2014c).…”
Section: Introductionmentioning
confidence: 99%